Innovation et intervention sociales (Seismo, 2024)
Innovation has long been associated with technology alone. This edited volume describes the development of social innovation in the social and health sectors, mainly in French-speaking Switzerland, and discusses the different ways in which it is conceptualised and understood. The aim of the book is to give visibility to initiatives implemented in contexts as diverse as socio-professional integration, homelessness, palliative care, psychiatry and child protection. It is aimed at anyone who wants to understand what social innovation is, some of its methods and tools, as well as the obstacles it can face and some of its positive effects, such as social cohesion in an urban environment, support for elderly people suffering from dementia or parenting support in the context of addiction.